PROSPEK PENDAFTARAN INDIKASI GEOGRAFIS PADA PRODUK KERAJINAN INDUSTRI KECIL MENENGAH (IKM) SANGIRAN KABUPATEN SRAGEN PROVINSI JAWA TENGAH - Triyono Adi Saputro; Suharno Suharno; Ariy Khaerudin (Universitas Janabadra, 2018)
Geographical indications is a trade name associated on the packaging of the product function shows the origin of a product, where the place of origin of the product quality hinting strongly influenced by place of origin so that the product is unique value. Small and medium industry Sangiran is one of a small industrial area of Sragen which has a special quality because it is affected by natural factors, human and combinations that are able to create products unique and special characters. The prospect of the registration of a geographical indication on the small and medium industry handicraft product Sangiran Sragen is very promising because small and medium industry totaled sixty scattered in Sragen variations craft products products generated. For that, the indispensable role of Government in the implementation of the registration of a geographical indication on the small and medium industry handicraft products Sangiran Sragen to get legal protection and has a reputation that can enhance competitiveness of the region Sragen. Keywords: Geographical Indications, Small Medium Industry, Legal Protection, Sangiran.